1996
DOI: 10.21836/pem19960327
|View full text |Cite
|
Sign up to set email alerts
|

Protein, amino acid and energy requirements of weanling foals and yearlings

Abstract: SummaryWeanling foals are sensitive to the quaiity of dietary protein, i.e. amino acid supply. Lysine and threonine have been indicated as the two firsi limiting amino acids for growth, but data on other amino acids are inadequate for establishing any accurate recommendations. Dietary protein quality has been reported to influence the amino acid profile of serum, and the blood amino acid concentrations and amino acid intakes reported in certain studles may have some value as guidelines in determining the amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, the Treiber et al (2005) weanling study did not evaluate the effect of diet on the incidence of OC, assessed either by clinical signs of lameness or radiographic evaluation. Consistent with these findings, lysine and threonine have been suggested as the two first limiting amino acids for growth in foals (Ott et al 1981, Graham et al 1994, Saastamoinen 1996. Ott et al (2005) did not find that feeding a high starch concentrate intake for 112 days (>30% and glycine reduced either the overall OC score or the OC severity score in pigs (Frantz et al 2008).…”
Section: Quantity and Quality Of Energy Intakementioning
confidence: 89%
“…However, the Treiber et al (2005) weanling study did not evaluate the effect of diet on the incidence of OC, assessed either by clinical signs of lameness or radiographic evaluation. Consistent with these findings, lysine and threonine have been suggested as the two first limiting amino acids for growth in foals (Ott et al 1981, Graham et al 1994, Saastamoinen 1996. Ott et al (2005) did not find that feeding a high starch concentrate intake for 112 days (>30% and glycine reduced either the overall OC score or the OC severity score in pigs (Frantz et al 2008).…”
Section: Quantity and Quality Of Energy Intakementioning
confidence: 89%
“…Other methods proposed in Germany, The Netherlands, or Scandinavia depict different dynamics of protein requirement from 6 to 18 mo of age, although in the range of 6 to 12 mo of age, the German system follows a pattern similar to the NRC system and the other 2 systems are closer to the INRA requirements (Martin-Rosset and Ellis, 2005). However, in spite of these different dynamics in CP requirement suggested by different feeding standards, it has been reported that optimal growth can be obtained with a CP concentration in the diet ranging from 12 to 17% (Saastamoinen, 1996;Staniar et al, 2001). However, most of studies have been performed considering light breeds and standard requirements for the heavy draft breeds have been reported only by the French system (Martin-Rosset and Ellis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to either positive or negative consequences on animal growth, obviously also in horses, depending on the feed quality and energy requirements (Lewis, 1996;Pagan, 2009). Whereas studies on CP level on the growth of light horses have been already performed (e.g., Graham-Thiers et al, 1999;Staniar et al, 2001), literature on heavy breeds is scarce, although information on other coldblood breeds have been previously reported (Saastamoinen, 1996).…”
Section: Introductionmentioning
confidence: 99%